Pengembangan Gamifikasi Pada Modul E - Learning Service Excellence Untuk Karyawan Frontliner - Ferdy Achmad Zulfikar; Akhmad Unggul (Jurnal Inovasi Informatika, 2022)
This paper is to develop teaching materials in the form of developing gamification teaching materials in the service excellence module that will be used for frontliner employees. The purpose of this research is to design the development of gamification teaching materials in the service excellence module that can be used for frontliner employees. The research results from the results of designing and testing gamification teaching materials for the service excellence module for frontlinner mall employees on a limited scale, that the feasibility of the content of the material and the feasibility of presenting gamification obtained an average score of 80%. Validation of the content of the Service Excellence module using gamification obtained an average score of 81%, and validation of the feasibility of presenting the Service Excellence module using gamification obtained an average score of 78%, so the survey results from the trial show that the teaching materials in the E-learning Service module Excellence carried out using gamification is suitable for use in training activities